Fabrication and Assessment of ZnO Modified Polyethersulfone Membranes for Fouling Reduction of Bovine Serum Albumin - Tshepo Duncan Dipheko; Kgabo Philemon Matabola; Kate Kotlhao; Richard M. Moutloali; Michael Klink (International Journal of Polymer Science)
ZnO/PES composite membranes were fabricated by phase inversion method using DMAc as a solvent. The structure of ZnO was investigated using TEM, SEM, XRD, and TGA. TEM images of ZnO nanoparticles were well-defined, small, and spherically shaped with agglomerated nanoparticles particles of 50 nm. The SEM and XRD results were an indication that ZnO nanoparticles were present in the prepared ZnO/PES composites membranes. Contact angle measurements were used to investigate surface structures of the composite membranes. The amount of ZnO nanoparticles on PES membranes was varied to obtain the optimal performance of the composite membranes in terms of pure water flux, flux recovery, and fouling resistance using the protein bovine serum albumin (BSA) as a model organic foulant. The results showed that addition of ZnO to PES membranes improved the hydrophilicity, permeation, and fouling resistance properties of the membranes. Pure water flux increased from a low of 250 L/m2h for the neat membrane to a high of 410 L/m2h for the composite membranes. A high flux recovery of 80–94% was obtained for the composite membranes. The optimal performance of the composite membranes was obtained at 1.5 wt% of ZnO.